Pengaruh Harga, Kualitas Produk, Citra Merek, Promosi, Dan Ketersedian Produk Terhadap Keputusan Pembelian Konsumen Pada PT. Millennium Pharmacon International TBK. Cabang Jember - Ahmad Andrianto; Nely Supeni; Ahmad Sauqi (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the influence of price, product quality, brand image, promotion, and product availability on consumers' purchasing decisions at PT Millennium Pharmacon International Tbk, Jember Branch. The study employed a quantitative research approach with a sample of 60 respondents. Data were collected through observation and questionnaires, while multiple linear regression analysis was used to examine the relationships among the variables. The sample was selected using a purposive sampling technique, and the data were analyzed using the Statistical Package for the Social Sciences (SPSS). The results indicate that product quality has a positive and significant effect on consumers' purchasing decisions. Meanwhile, price, brand image, promotion, and product availability do not have a significant effect on purchasing decisions. This study concludes that product quality is the most influential factor in enhancing consumers' purchasing decisions at PT Millennium Pharmacon International Tbk, Jember Branch